Freedom of Expression in Islam: Challenging Apostasy and Blasphemy Laws - Masud, Muhammad Khalid (I. B. Tauris & Company, Limited, 2021)
Cover page -- Halftitle page -- Title page -- Copyright page -- Contents -- List of Contributors -- Acknowledgements -- A Note on Transliteration -- Introduction -- Mapping blasphemy and apostasy laws -- Repression, freedom and religious justification -- Islamic legal terms -- International standards -- Structure of the book -- Notes -- Part One The Historical Construction -- 1 Blasphemy Laws in Islam Towards a Rethinking? -- Blasphemy in religious traditions -- Blasphemy in Islamic tradition: An overview -- Blasphemy in the Qurʾan and Sunna -- The development of blasphemy laws in Islam -- The rethinking of blasphemy laws -- Concluding remarks -- Notes -- 2 Freedom of Religion in Qurʾanic Exegesis -- Introduction -- Classical exegetical works -- Modern exegetes -- Contemporary Muslim views -- Conclusion -- Notes -- 3 al-Qadi ʿIyad's Defence of the Prophet and of Scholarly Tradition: al-Shifāʾ -- Al-Qadi ʿIyad -- The Shifāʾ -- The title, structure and content of the Shifāʾ -- ʿIyad's sources for the Shifāʾ -- The rights of the Prophet: On faith, love and obedience -- Rights of the Prophet: On denigration and insult -- Legal discourse and practice -- Socio-political context and possible functions of the text -- Epistemic authority, judicial reasoning and infallibility -- Concluding remarks -- Notes -- 4 Reading Ibn Taymiyya's al-S.ārim: Hermeneutic Shifts in the Definition of Blasphemy -- Historical context -- Personal context -- Doctrinal context -- Reading al-S.ārim al-Maslūl -- Ibn Taymiyya's jurisprudence -- Conclusion -- Notes -- Part Two Present Practices -- 5 The Crimes of Blasphemy and Apostasy in Iran -- Cases -- Apostasy and blasphemy in Iran's legal system -- Apostasy in Iran's penal code -- Grounds for defence -- Application of the law to the mentioned cases -- Conclusion -- Notes.